A Cluster of Fluconazole-Resistant Malassezia pachydermatis in a Neonatal Intensive Care Unit — California, 2015–2016. (4th October 2017) - Chinn, Raymond; Pong, Alice; Schultz, Kerry; Kim, Janice; Kaegi, David; Rasmussen, Maynard; Woerle, Cathy; Malagon-Maldonado, Gabriela; Neder, Charlyne; Beer, Karlyn; Chow, Nancy; Glowicz, Janet; et al.
Abstract: Background: Malassezia pachydermatis, a common veterinary yeast, rarely causes outbreaks in neonatal intensive care units (NICUs). One outbreak was associated with healthcare worker (HCW) colonization with strains shared by pet dogs. Prevention relies on good hand hygiene, but data HCW pet ownership and interaction are lacking. We report a cluster of 5 cases of M. pachydermatis infection or colonization during December 2015–September 2016 in a Level 3, 84-bed NICU and results of a HCW survey on hand and pet-related hygiene. Methods: A case was defined as a culture yielding M. pachydermatis from sterile sites or skin of a NICU patient. We used whole-genome sequencing (WGS) to examine genetic relatedness among the 5 M. pachydermatis isolates compared with 9 isolates in CDC's historical collection. As part of a series of NICU hand hygiene improvement campaigns, we administered a web-based survey of hand hygiene practice, pet ownership, and pet health to 290 NICU HCWs employed while case-patients were admitted. Results: We identified 5 cases (3 fungemias, 1 infected urinoma, 1 colonization) during the 9-month period (Figure 1), and a hospital lookback revealed no M. pachydermatis infections before the first case. All patients had low birth weight, central venous or peripheral arterial catheters, prior broad-spectrum antibiotics, and antifungal prophylaxis. All isolates were resistant to fluconazole and were highly related by WGS (<14 single-nucleotide polymorphisms [SNPs]) but unrelated to historical isolates (>40, 000 SNPs). Survey respondents ( N = 151[52%]; Figure 2) reported perceived peer HCW hand hygiene lower than their own, and 69% reported daily contact with dogs or cats. Survey results did not differ among staff who did ( n = 15) and did not ( n = 136) care for all case patients. No cases were reported in the 7 months following the fifth case. Conclusion: We report a NICU cluster of fluconazole-resistant M. pachydermatis cases nearly identical by WGS, suggesting a common source of infection, possibly related to HCW carriage following contact with household pets. A hygiene improvement campaign may have mitigated further transmission. M. pachydermatis is a potential cause of fungemia among neonates on fluconazole prophylaxis. Disclosures: All authors: No reported disclosures.